RAPID framework for improved access to precision oncology for lethal disease: Results from a modified multi-round delphi study - Bright, Kristin; Mills, Anneliese; Bradford, John-Peter; Stewart, David J. (Frontiers in Health Services, 2023)
INTRODUCTION: Predictive oncology, germline technologies, and adaptive seamless trials are promising advances in the treatment of lethal cancers. Yet, access to these therapies is stymied by costly research, regulatory barriers, and structural inequalities worsened by the COVID-19 pandemic. METHODS: To address the need for a comprehensive strategy for rapid and more equitable access to breakthrough therapies for lethal cancers, a modified multi-round Delphi study was conducted with 70 experts in oncology, clinical trials, legal and regulatory processes, patient advocacy, ethics, drug development, and health policy in Canada, Europe, and the US. Semi-structured ethnographic interviews (n=33) were used to identify issues and solutions that participants subsequently evaluated in a survey (n=47). Survey and interview data were co-analyzed to refine topics for an in-person roundtable where recommendations for system change were deliberated and drafted by 26 participants. RESULTS: Participants emphasized major issues in patient access to novel therapeutics including burdens of time, cost, and transportation required to complete eligibility requirements or to participate in trials. Only 12% of respondents reported satisfaction with current research systems, with “patient access to trials” and “delays in study approval” the topmost concerns. CONCLUSION: Experts agree that an equity-centered precision oncology communication model should be developed to improve access to adaptive seamless trials, eligibility reforms, and just-in-time trial activation. International advocacy groups are a key mobilizer of patient trust and should be involved at every stage of research and therapy approval. Our results also show that governments can promote better and faster access to life-saving therapeutics by engaging researchers and payors in an ecosystem approach that responds to the unique clinical, structural, temporal, and risk-benefit situations that patients with life-threatening cancers confront.